First passenger train of the White Pass & Yukon Railroad en route to the summit, Alaska, February 20, 1899. - Hegg, Eric A., 1867-1948 (1899)
Shows train and passengers stopped on a trestle bridge. Caption on image: "First passenger train over White Pass and Yukon Route to summit. Feb 20 1899" Original image in Hegg Album 7, page 34.